2017
DOI: 10.1111/jonm.12510
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of nursing workforce planning and forecasting research

Abstract: Accurate nursing workforce forecasting can help nurse managers, administrators and policy makers to understand the supply and demand of the workforce to prepare and maintain an adequate and competent current and future workforce.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 42 publications
1
31
0
1
Order By: Relevance
“…However, the findings of this study point to a systematic failure across all sectors to regulate workload and therefore care delivery. With the exception of rural and remote health facilities, which have historically had difficulties recruiting staff (Hegney, McCarthy, Rogers‐Clark, & Gorman, ; Squires, Jylha, Jun, Ensio, & Kinnunen, ), the perceptions were that insufficient staff employed was driven not by supply (Squires et al, ), but by fiscal constraint.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the findings of this study point to a systematic failure across all sectors to regulate workload and therefore care delivery. With the exception of rural and remote health facilities, which have historically had difficulties recruiting staff (Hegney, McCarthy, Rogers‐Clark, & Gorman, ; Squires, Jylha, Jun, Ensio, & Kinnunen, ), the perceptions were that insufficient staff employed was driven not by supply (Squires et al, ), but by fiscal constraint.…”
Section: Discussionmentioning
confidence: 99%
“…It would mean, however, that managers would need to be more assertive in speaking out regarding clinical workloads, a matter that Perron argues, should be part of a manager's job (Perron, ). In times of actual and predicted nurse shortages, nurse managers can directly influence the willingness or otherwise of nurses to work for an individual health service and this can lead to poor nurse retention (Squires et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…We argue that similar to the case of nursing staff shortages [45], specific models for workforce forecasting with regard to social workers will be gaining in importance and recognition. Effective forecasting models help managers and policy and decision makers to predict possible shortages or excesses of workforce and its consequences for organizational activities such as planning of activities and annual budgets [45]. Actual data from 2015 show that the European Union had the second highest old-age dependency ratio (29.2%) after Japan (42.7%).…”
Section: Introductionmentioning
confidence: 92%
“…In addition, research has shown that a considerable number of nurses experience high levels of job stress, which increases sickness absence and puts pressure on the remaining nurses causing a vicious circle of absenteeism (Van den Heede et al, ; Trybou et al, ). Evidence‐based decision‐making linking nurse staffing with constantly changing patients' care needs is therefore a much needed area of expertise (Squires, Jylha, Jun, Ensio, & Kinnunen, ).…”
Section: Introductionmentioning
confidence: 99%